Novel Medicine : Healing, Literature, and Popular Knowledge in Early Modern China - Schonebaum, Andrew, 1975- (Book collections on Project MUSE., 2016)
"Printed novels, guides to daily life, and practical medical texts were relatively new in sixteenth-century China, but they quickly became popular and influential. Novel Medicine shows how fiction shaped and was shaped by medical discourse and how it popularized practical, vernacular kinds of knowledge. A vibrant exchange among literary, commercial, and medical spheres resulted in a web of texts that produced distinct genealogies of romantic and sexual disease, iconographic lineages of heroic doctors, and medicalized attitudes toward reading. Novel Medicine interrogates how fiction incorporated, created, and disseminated medical knowledge. Conversely, it demonstrates how practical medical texts employed literary devices and figurative strategies to propagate information. Employing interdisciplinary strategies, it examines the dynamic interplay between discourses of fiction and medicine as well as their representations of illnesses and healers. Critical readings of fictional and medical texts, as well as sources such as fiction commentary, criticism, medical manuscripts, newspapers, essays, print images, and biographies inform an understanding of the body in early modern China. These readings also provide a counterpoint to prevailing narratives that focus on the 'literati' aspects of the novel, showing that these texts were not merely read, but were used by a wide variety of readers and for a range of purposes. This inquiry into the intersections of kinds and sources of knowledge--fictional and real, elite and vernacular--illuminates the history of reading and daily life and challenges us to rethink the nature of Chinese literature"--Provided by publisher.